2019
DOI: 10.1016/j.humimm.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Association of pro-inflammatory cytokines and monocyte subtypes in older and younger patients on clinical outcomes after mechanical circulatory support device implantation

Abstract: Noninvasive immunologic analysis of peripheral blood holds promise for explaining the mechanism of development of adverse clinical outcomes, and may also become a method for patient risk stratification before or after mechanical circulatory support device (MCSD) implantation. Dysregulation of the innate immune system is associated with increased patient age but has yet to be evaluated in the older patient with advanced heart failure undergoing MCSD surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Indeed, we reported that the expression of TLR-4 was lower in both the LBW-CHF and LBW-HFDairy groups while the LBW-LFDairy was similar to NBW-Chow. Decreased expression of TLR-4 has been previously reported in elderly patients who have a higher prevalence of infection than younger patients (49). In contrast, B cell proportions were previously found to be similar in individuals with obesity and T2D compared to MHO (7).…”
Section: Dairy and Their Impact On Peripheral Blood Apc Functionmentioning
confidence: 84%
“…Indeed, we reported that the expression of TLR-4 was lower in both the LBW-CHF and LBW-HFDairy groups while the LBW-LFDairy was similar to NBW-Chow. Decreased expression of TLR-4 has been previously reported in elderly patients who have a higher prevalence of infection than younger patients (49). In contrast, B cell proportions were previously found to be similar in individuals with obesity and T2D compared to MHO (7).…”
Section: Dairy and Their Impact On Peripheral Blood Apc Functionmentioning
confidence: 84%
“…Screening of full-text articles identified a total of 45 studies that met eligibility criteria. 17–61 Search results and study selection are summarized in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Nine (8 noncardiac and 1 cardiac) reported an association between biomarker levels and our secondary outcomes of mortality and surgical or medical complications. 17,19,25,26,29,33,46,56,57 A formal meta-analysis of secondary outcomes was not possible as few studies reported these relationships and due to heterogeneity in outcome reporting. However, a narrative summary of the relationships between biomarkers and secondary outcomes investigated by each study is reported in Supplemental Digital Content 1, Appendixes 16–19, http://links.lww.com/AA/D747.…”
Section: Resultsmentioning
confidence: 99%
“…Immunological or cytokine reaction after the MCS implant may the one of the reasons leading to this finding. 17,18 Although there may be many issues or confounding factors, the activated reaction might cause the subsequent response to the recipients under critical status and have the greatest impact on the outcome. This finding might echo a philosophical reflection: Action taken in the proper time results in a proper outcome.…”
Section: Discussionmentioning
confidence: 99%